PENGUATAN PERAN LEMBAGA ADAT DALAM PELESTARIAN ADAT ISTIADAT DI DESA PULAU RAJAK KABUPATEN BANYUASIN - Muhammad Nur Amin; Fatria Khairo; Erleni Erleni; Dede Riansya Putra (Sumpah Pemuda : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted to strengthen the understanding of the Pulau Rajak Village community in Banyuasin Regency regarding the role of customary institutions in preserving customary traditions and local wisdom. The background of this activity is based on the importance of customary law in the social life of South Sumatran communities, including the legal tradition derived from the Simbur Cahaya Law as one of the written customary legal references historically applied in Palembang society. In the context of Banyuasin Regency, the existence of customary law communities and the compilation of customary traditions have been recognized through Banyuasin Regency Regional Regulation Number 9 of 2012. This activity aims to provide education to village officials, customary leaders, community figures, and residents regarding the function of customary institutions as a medium for preserving traditions, maintaining socio-cultural values, and resolving social issues through deliberation. The method used an educational-participatory approach through socialization, discussion, identification of local customary values, institutional assistance, and evaluation of participants’ understanding. The results show an increase in participants’ understanding of the importance of customary institutions in preserving customary traditions, strengthening social harmony, and maintaining the cultural identity of the Pulau Rajak Village community. This activity is expected to encourage the strengthening of village customary institutions as part of the sustainable preservation of Banyuasin customary traditions.